2022
DOI: 10.1051/0004-6361/202243278
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter in galaxy clusters: Parametric strong-lensing approach

Abstract: Context. We present a parametric strong-lensing analysis of three massive galaxy clusters for which Hubble Space Telescope imaging is available, as well as spectroscopy of multiply imaged systems and galaxy cluster members. Our aim is to probe the inner shape of dark matter haloes, in particular the existence of a core. We adopted the following working hypothesis: any group-or cluster-scale dark matter clump introduced in the modelling should be associated with a luminous counterpart. We also adopted some addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Of the two values, one is given without an error estimate (Manjón-García et al 2020) and the other is zero, and significantly smaller than the NFW value (S04). The result of S04 is supported by the strong lensing analysis of Limousin et al (2022), who find that a cored inner mass density profile is a better fit to the data than a cuspy model.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Of the two values, one is given without an error estimate (Manjón-García et al 2020) and the other is zero, and significantly smaller than the NFW value (S04). The result of S04 is supported by the strong lensing analysis of Limousin et al (2022), who find that a cored inner mass density profile is a better fit to the data than a cuspy model.…”
Section: Introductionmentioning
confidence: 67%
“…They found that a cored DM halo reproduces the observed kinematics better than an NFW profile. Based on a strong lensing analysis of three clusters, Limousin et al (2022) find that cored inner mass density profiles are favored over cuspy models. Using a combination of strong gravitational lensing and BCG kinematics, Newman et al (2013b) estimate γ DM = 0.50 ± 0.13 averaging over seven clusters, in agreement with previous results by the same collaboration (Sand et al 2002(Sand et al , 2008Newman et al 2009Newman et al , 2011.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Perhaps the model could have both a4 and b4 perturbations, varying as a function of radius. Cluster-scale models frequently use a soft core inside some scale radius, and (Limousin et al 2022) add B-spline functions. The number of free parameters must be balanced with the information available: pixellated mass models are generally underconstrained (and although they might be able to fit observations without external shear; Valls-Gabaud et al 2006, some lineof-sight shear is expected for galaxy-scale lenses).…”
Section: Implications For Strong Lensing Science Goalsmentioning
confidence: 99%
“…Subsequent papers have even proposed using external shear as relatively high signal-to-noise measurements of the 'cosmic' shear along individual lines of sight (Birrer et al 2017;Desprez et al 2018;Kuhn et al 2020;Fleury et al 2021;Hogg et al 2022). However, the best-fit values of external shear did not match the lines of sight to the three other galaxies studied by Wong et al (2011) -and, in general, best-fit values are much larger than expected for both galaxy lenses (Keeton et al 1997;Witt & Mao 1997;Hilbert et al 2007;Suyu et al 2010;Barrera et al 2021) and cluster lenses (Robertson et al 2020;Limousin et al 2022). Using mock observations, Cao et al (2022, hereafter C22) demonstrated that the best-fit shear can be incorrect if the model of the mass distribution is missing complexity.…”
mentioning
confidence: 94%